Dielectric analysis of degraded stator bars of a hydro generator - Norasage Pattanadech; N. Phumipunepon; Chissanupong Srinangyam; Siwakorn Jeenmuang; Chanin Bunlaksananusorn (Energy Reports, 2021)
This paper presents the investigation of dielectric analysis of degraded stator bars by Polarization and Depolarization Current (PDC) measurement. The stator bars obtained from the 30-year in-service synchronous machine were divided into two groups. The first group was the unmodified stator bars. The second group was the simulated degradation stator bars which were composed of the thermal stress stator bars, conductive tap abrasion stator bars, multiple air cavity stator bars, multiple oil filled stator bars and multiple water filled stator bars. PDC test experiment was performed with the stator bar samples. PDC test results were analyzed in time domain and in frequency domain with the derived parameters i.e. Rdc, real and imaginary part of complex capacitance, C ratio, conduction loss factor and polarization loss factor. It was found that PDC shapes obtained from the conductive tape abrasion stator bar and multiple water filled cavity stator bar were clearly different from that of the unmodified stator bar. For other case studies, the derived parameters showed the usefulness in analysis the degraded stator bar characteristics. For example, the increase in the imaginary capacitance and conduction loss factor can be observed from most cases of degraded stator bar test results.
Keywords: High voltage insulation and dielectric phenomena; Power Transformer Diagnostics and Insulation; Lightning and Electromagnetic Phenomena